Gesturing makes memories that last - Cook, Susan Wagner (2010)
When people are asked to perform actions, they remember those actions better than if they are asked to talk about the same actions. But when people talk, they often gesture with their hands, thus adding an action component to talking. The question we asked in this study was whether producing gesture along with speech makes the information encoded in that speech more memorable than it would have been without gesture. We found that gesturing during encoding led to better recall, even when the amount of speech produced during encoding was controlled. Gesturing during encoding improved recall whether the speaker chose to gesture spontaneously or was instructed to gesture. Thus, gesturing during encoding seems to function like action in facilitating memory.